Dimensi Sosial Ekaristi Yohanes Paulus II dan Benediktus XVI - Dwi Andri Ristanto (Jurnal Teologi (Journal of Theology), 2020)
Concerns that arise currently are the development of a culture of hatred, the fading of a culture of love, secularism and social injustice. In the midst of that situation, the Church stands as a concrete manifestation of the face of God's love in the middle of the world. In the Ecclesia de Eucharistia encyclical, John Paul II asserted that the eschatological character emphasize the Christian commitment to the world, especially establish the social life order (cf. EE 20). The Eucharistic dimension of the Eucharist implies that the world order must be transformed as a form of participation towards fulfillment at the end of time. Whereas in the Apostolic Exhortation Sacramentum Caritatis, Benedict XVI, asserted that the Eucharist celebration brings our whole lives into spiritual worship that pleases to God (cf SCar 70). From this research, it is known that the Eucharistic social dimension becomes a spirit of love culture according to the writer. This love culture finds its source and power in the Eucharist. Through the celebration of the Eucharist, people are mystically united with Christ. In the light of the theology of the Eucharistic social dimension of John Paul II and Benedict XVI, mystical union with Christ refers to the oneness of God's thankfulness to the fulfillment of the last days (cf. John 15:13).